A classification framework for data marketplaces - Lara Vomfell; Florian Stahl; Fabian Schomm; Gottfried Vossen (Westfälische Wilhelms-Universität Münster, European Research Center for Information Systems (ERCIS), 2015)
Trading data as a commodity has become increasingly popular in recent years, and data marketplaces have emerged as a new business model where data from a variety of sources can be collected, processed, enriched, bought, and sold. They are effectively changing the way data is distributed and managed on the Internet. To get a better understanding of the emergence of data marketplaces, we have conducted several surveys in recent years in order to systematically gather and evaluate their characteristics. This paper takes a broader perspective and relates data marketplaces to the neoclassical notions of market and marketplace from economics. We provide a typology of electronic marketplaces, and discuss their approaches to a distribution of data. Lastly, we provide a distinct definition of data marketplaces in order to integrate these new businesses into existing research frameworks, leading to a classification framework that can help structuring this emerging field.
Keywords: 650; Data as a Service; Data Marketplace; Data Marketplace Survey; Data Marketplace Development; Classification